Exploring facets of trust in older adult decisions to adopt mobile commerce - J. Morga Ph. D, John; S. M. Rahman Ph. D, Shawon (International Journal of Engineering and Technology, 2018)
Mobile commerce currently suffers from low adoption rates even though mobile devices are seemingly everywhere. Retailers have not fully tapped the older adult consumer market, a market framed by two significant attributes. Firstly, older adults are currently the largest segment of the USA population and will be for many years. Secondly, older adults are already known to be a lucrative market for low debt their spending power make them a primary interest to online retailers. While research exists for mobile commerce technology, the older adult age group has not yet been a primary focus of exploration. This quantitative study specifically examined aspects of mobile device usage, privacy, and internet trust factors of mobile commerce adoption among older adults by adapting modern technology acceptance theory as the frame-work for the research. This study determined that older adults have similar levels of interest in mobile commerce technology as compared to younger consumers but approach new technology cautiously, with a deeper consideration of risks and consequences.Â Â